FORMATION OF ASTRONOMICAL MOTIVATION AND RESEARCH SKILLS FOR SCHOOLCHILDRENS OF GRADES 11 - Saydayev Obid Bahodir o‘g‘li (Web of Journals Publishing, 2025)
The paper examines the issue of developing schoolchildrens' interest in research activities in astronomy, professional orientation of students, and systematic preparation for Olympiads in the subject. It was shown that the task of astronomy, like any natural science subject studied in primary school or at the basic level in high school, is the formation of natural science literacy. Increasing the basic level of astronomical literacy is necessary for the full life of each person in modern society, adequate perception of heterogeneous information in modern information flows, the formation of skills in using natural science and physical and mathematical knowledge for object analysis of the structure of the surrounding world using the example of the achievements of modern astrophysics, astronomy and cosmonautics.
Keywords: Astronomers and cosmonautics, astronomical literacy, formation.